CONSTRUCTION OF RESIDENTIL BUILDINGS AND ITS IMPACT ON ENVIRONMENT - Samdani, Parth; Choudhary, M.P. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
A close coordination between environmental engineers and the construction industry has resulted in an environmental profiling system that enables designers and constructors to select materials and components with the lowest environmental impact. Construction has long been recognised as one of the most resource-hungry and the least sustainable industries in the world. However we continue to depend on buildings of all kinds – our homes, offices, hospitals, shops, cultural centres and more. Despite increasing awareness of the need to develop a sustainable approach within the construction industry, this proved difficult without a reliable method of evaluating and comparing the environmental impacts of different construction materials